Shifted Chebyshev schemes for solving fractional optimal control problems. (August 2019) - Abdelhakem, M; Moussa, H; Baleanu, D; El-Kady, M
Two schemes to find approximated solutions of optimal control problems of fractional order (FOCPs) are investigated. Integration and differentiation matrices were used in these schemes. These schemes used Chebyshev polynomials in the shifted case as a functional approximation. The target of the presented schemes is to convert such problems to optimization problems (OPs). Numerical examples are included, showing the strength of the schemes.